Migration and health: Exploring the effect of destinations on the health outcomes among rural-urban migrants in India - Bhan, Tanushree; Patel, Amit (Social science & medicine (1982), 2023)
Conservative estimates of the census of India pegged the number of rural-urban migrants at 78 million, out of the total internal migrant population of 456 million, in 2011. Despite their sizable number, larger than several European nations, very little is known about whether the type of urban destination matters for the physical health of these largely poor populations. Using data from two waves of the India Human Development Survey (2004–05 and 2011–12), we conduct multi-level analyses to explore the impact of metropolitan versus non-metropolitan destinations on the odds of short-term and long-term illnesses among rural-urban migrants across residential durations. Findings show that rural-urban migrants to metropolitan cities experience higher likelihood of suffering from overall and pollution-related major illnesses relative to their counterparts in non-metropolitan urban areas. On the other hand, migrants to metropolitan cities experience lower odds of suffering from minor illnesses than non-metropolitan rural-urban migrants. However, these significant effects of urban destination disappear when we compare health outcomes between shorter versus longer-duration migrants. We subject these multi-level analytic findings to robustness checks that corroborate our foregoing mixed results. Our findings generate initial evidence on health disparities among rural-urban migrants by destination and duration. These findings underscore the importance of health needs among migrant populations, that require attention particularly in the short-term of their relocation to cities. •Health disparities among rural-urban migrants in India by destination.•Disparities among rural-urban migrants fade away over longer duration of residence.•Environmental factors like air quality have limited explanatory power.•Multi-level analyses of health outcomes in migrants nested in districts within states.•Diagnostic checks for selection bias in choice of urban location by rural emigrants.